Enhancing the thermoelectric power factor of Sr0.9Nd0.1TiO3 through control of the nanostructure and microstructure. Issue 48 (30th November 2018) - Ekren, Dursun; Azough, Feridoon; Gholinia, Ali; Day, Sarah J.; Hernandez-Maldonado, David; Kepaptsoglou, Despoina M.; Ramasse, Quentin M.; Freer, Robert
Abstract : Doping with zirconia controls A site cation ordering in Sr0.9 Nd0.1 TiO3 and significantly enhances the thermoelectric power factor. Abstract : Donor-doped SrTiO3 ceramics are very promising n-type oxide thermoelectrics. We show that significant improvements in the thermoelectric power factor can be achieved by control of the nanostructure and microstructure. Using additions of B2 O3 and ZrO2, high density, high quality Sr0.9 Nd0.1 TiO3 ceramics were synthesised by the mixed oxide route; samples were heat treated in a single step under reducing atmosphere at 1673 K. Synchrotron and electron diffraction studies revealed an I 4/ mcm tetragonal symmetry for all specimens. Microstructure development depended on the ZrO2 content; low level additions of ZrO2 (up to 0.3 wt%) led to a uniform grain size with transformation-induced sub-grain boundaries. HRTEM studies showed a high density of dislocations within the grains; the dislocations comprised (100) and (110) edge dislocations with Burger vectors of d (100) and d (110) respectively. Zr doping promoted atomic level homogenization and a uniform distribution of Nd and Sr in the lattice, inducing greatly enhanced carrier mobility. Transport property measurements showed a significant increase in the power factor, mainly resulting from the enhanced electrical conductivity while the Seebeck coefficients were unchanged. In optimised samples a power factor of 2.0 × 10 −3 W m −1 K −2 was obtained at 500 K. This is an ∼30% improvement compared to the highest values reported for SrTiO3 -based ceramics. The highest ZT value for Sr0.9 Nd0.1 TiO3 was 0.37 at 1015 K. This paper demonstrates the critical importance of controlling the structure at the atomic level and the effectiveness of minor dopants in enhancing the thermoelectric response.